2020
DOI: 10.1016/j.psj.2019.12.066
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial diversity of Yoruba and Fulani chickens: A biodiversity reservoir in Nigeria

Abstract: Poultry are the most widely distributed type of livestock in Nigeria. Indigenous chickens are extremely common throughout the country. Indeed, approximately 83 million chickens are raised in extensive systems and 60 million in semi-intensive systems. To provide the first comprehensive overview of the maternal lineages in Southwest Nigeria, we analyzed 96 mitochondrial DNA control region sequences from 2 indigenous chicken ecotypes: Fulani and Yoruba. All samples belonged to the most frequent haplogroup (E) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…Four of the five haplogroups observed in the current study (A, B, D and E), were previously reported by Mtileni et al (2011b). Although this work reveals for the first time haplogroup C in South African populations, it was previously described in other African countries such as Kenya, Madagascar (Herrera et al 2017), Nigeria (Lasagna et al 2020) and Ethiopia (Al-Jumaili et al 2020). It is known that haplogroup E is one of the haplogroups showing ubiquity on chicken mtDNA profile globally.…”
Section: Findings Withsupporting
confidence: 70%
See 1 more Smart Citation
“…Four of the five haplogroups observed in the current study (A, B, D and E), were previously reported by Mtileni et al (2011b). Although this work reveals for the first time haplogroup C in South African populations, it was previously described in other African countries such as Kenya, Madagascar (Herrera et al 2017), Nigeria (Lasagna et al 2020) and Ethiopia (Al-Jumaili et al 2020). It is known that haplogroup E is one of the haplogroups showing ubiquity on chicken mtDNA profile globally.…”
Section: Findings Withsupporting
confidence: 70%
“…The use of molecular markers can provide quantified criteria for assessing genetic diversity, either within or between populations (FAO 2009). Microsatellites and mitochondrial DNA (mtDNA) are markers used to investigate genetic makeup for many domestic animals (Groeneveld et al 2010;Di Lorenzo et al 2015;Lasagna et al 2020). These markers complement each other to provide a more relevant reflection of population genetic makeup and its relationship with other populations (Ceccobelli et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the North Eastern part of Nigeria, specifically Yobe State, it was reported that, there are 3.4 million chickens reared domestically (Annuar et al, 2008). Currently, the populations are sure to surpassed the previously reported figures by Annuar et al (2008), Francis et al (2016 and Lasagna et al (2017). Maiduguri, an area in the same region, employed mostly, the deep litter rearing system; although facing challenges including, bad housing, poor management practices, inadequate vaccination, and diseases resulting in high mortality rate.…”
Section: Introductionmentioning
confidence: 90%
“…One year after (in 2017), a higher population of 180 million chickens were estimated to exist in Nigeria, of which only 21% are intensively reared. Specifically, 83 million chickens are raised in extensive systems and 60 million in semi-intensive systems, most of which are indigenous chickens, contributing substantially to the nation's gross domestic product (GDP) (Lasagna et al, 2017). In the North Eastern part of Nigeria, specifically Yobe State, it was reported that, there are 3.4 million chickens reared domestically (Annuar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In developing and underdeveloped countries, indigenous chickens are more abundant, with Nigeria having the most among the Sub-Saharan countries ( 1 ). Nigerian indigenous chickens (NICs) are found in several geopolitical zones around the country and are classified according to genetic lines of feathering (normal feather, naked neck, and frizzle feather), color variants (black, white, brown, and mottled), and ecotypes [Yoruba (YRE) and Fulani (FLE)] ( 2 , 3 ). Both ecotypes are good scavengers and have excellent immunity against endemic diseases ( 4 ).…”
Section: Introductionmentioning
confidence: 99%